Alternative agriculture (National Academy Press, 1989)
Alternative Agriculture describes the increased use of these new practices and other changes in agriculture since World War II, and examines the role of federal policy in encouraging this evolution, as well as factors that are causing farmers to look for profitable, environmentally safe alternatives. Eleven case studies explore how alternative farming methods have been adopted--and with what economic results--on farms of various sizes from California to Pennsylvania.